Immunological Response as a Source to Variability in Drug Metabolism and Transport - Christensen, Hege; Hermann, Monica (Frontiers in Pharmacology, 2012)
Through the last decades it has become increasingly evident that disease-states involving cytokines affect the pharmacokinetics of drugs through regulation of expression and activity of drug-metabolizing enzymes, and more recently also drug transporters. The clinical implication is however difficult to predict, since these effects are dependent on the degree of inflammation and may be changed when the diseases are treated. The present article will give an overview of the present understanding of the effect of cytokines on CYP enzymes and drug transporters, and highlight the importance of considering these issues in regard to increasing use of the relatively new class of drugs, namely therapeutic proteins.